Synthesis of acridines via copper-catalyzed amination/annulation cascades between arylboronic acids and anthranils. Issue 48 (28th November 2022) - Li, Yuge; Xu, Liang; Wei, Yu
Abstract : The direct conversion of aryl boronic acids and anthranils to acridines has been realized herein, via the catalysis of copper species under acidic conditions. Abstract : Copper-catalyzed tandem cyclization reactions between arylboronic acids and anthranils have been established, providing new approaches for one-pot assembly of azacycle acridines. This one-pot protocol features simple operation, precious-metal-free conditions and good functional group compatibility, thus providing an efficient approach for the synthesis of a variety of acridines in moderate to good yields.